Dzishol’s Therapy With Slow Deep Breathing (SDB) to Overcome Mental Health in Postpartum Mothers in Semarang City - Fitriani, Ardhita Listya; Indah Wulaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Mothers who give birth tend to experience increased anxiety which can result in psychological disorders including anxiety, depression (Denis,2021). Postpartum psychological health disorders increase the risk of postpartum blues. The underlying factors are limited access to health services, lack of social support from various parties, and concerns about the health of herself and her baby that will be ignored by the mother. Social support helps postpartum mothers deal with stressors (Adli, 2022). This research method uses Quasi experimental with two groups pretest posttest research design. The sampling technique uses purposive sampling. The sample size consists of 30 participants divided into 2 groups with 15 respondents each. The intervention group received dhikr sholawat treatment while the control group only received slow deep breathing (SDB) treatment. The intervention lasted for 14 days. The measurement of depression levels carried out was a measurement using the Edinburgh Postnatal Depression Scale (EPDS) instrument form. The results of the study P value 0.023 (> 0.05) so it is concluded that there is a difference between the effectiveness of providing Dzishol intervention and SDB intervention. Based on the comparison of the median value after the intervention in the group, it is known that the median value in the Dzishol group (score 11) is smaller than the SDB group (score 9) so it can be concluded that providing Dzishol intervention on anxiety levels is more effective than SDB intervention.